Socioeconomic and environmental impacts of water markets: a literature review - Campanhão, Ligia Maria Barrios; Picharillo, Caroline; Ranieri, Victor Eduardo Lima; Okawa, Cristhiane Michiko Passos (Desenvolvimento e Meio Ambiente, 2021)
The water market is an economic instrument for the water allocation among different users, particularly in locations and periods of water scarcity. Although several authors defend the instrument as beneficial for the conservation and efficient use of water resources, other effects, such as issues of equity, sustainability and environmental impacts need to be assessed. This article focuses on identifying the economic, social and environmental impacts of water markets through a review of the literature. The searches were conducted in Scopus and Web of Science bases, where 235 studies were screened. 48 of these studies were included in the review, and most of them report only economic impacts, such as effects on landowners’ income, agricultural production and efficiency of water use. On the other hand, social and environmental impacts were poorly evaluated by the studies. Social impacts mainly include issues of distribution of market benefits and access to water and rights. Of the environmental impacts, the effects on the environmental flow of rivers and reservoirs, as well as on the levels in the aquifers, stand out. It is concluded that the literature is still incipient in documenting the impacts of water markets in terms of diversity of effects, and further studies are needed to assess environmental impacts and equity and justice in access to water.